A Mobile Health App for Premarital Related Word Advice (AmeeSehat): Usability and Usefulness Evaluation Study - Wiyanti , Zulvi; Oenzil, Fadil; Masrul, Masrul; Djafri, Defriman (Open Access Macedonian Journal of Medical Sciences, 2021)
Background:Premarital counseling demonstrates promising approach for enhancing interaction between couples and to prevent deterioration in the well-being of relationships. Mobile health (mHealth) apps may provide an appropriate solution to this issue, as many potential brides and grooms are frequent users of internet or web-based health info. Aim:This research aimed to measure the usability and usefulness of the AmeeSehat App as interpreted by potential end users. Method: This study employed a mixed method carried out in one of the public-health centers in East Jakarta, Indonesia with the future bride and groom. Think Aloud (TA) sessions with participants (n=10 final users and 3 experts) and quantitative assessment with 60 participants were held.A think aloud meetings have been captured, transcripts, and analyzed. The usability issues were evaluated using Nielsen severity scale and the Device Usability Scale (SUS). The usefulness of the AmeeSehat App was assessed using a tool to evaluate an improvement in healthy family knowledge, attitude, and intention, and readiness to marry. Results: The SUS score obtained (mean=78.4, SD=6.83), and none of the participants experienced (severe) problems with usability. Only 1 usability problems have been reported with a severity of 3 (major), namely terminology issues. The change after using AmeeSehat was statistically significant different as McNemar test revealed p <0.05. Conclusion:This researcher revealed that, in terms of its usability and usefulness, the AmeeSehat app is feasible to future brides and grooms. Participants considered AmeeSehat beneficial because they had the opportunity to learn more about a stable home life in preparation for marriage. Further assessment should be carried out in the form of a randomized controlled trial to test AmeeSehat's effectiveness in enhancing awareness, attitude, intention and readiness.